Penerapan Algoritma C4.5 Untuk Prediksi Jumlah Produksi Kelapa Sawit - Rahma Yuni; Raissa Amanda Putri (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Palm oil is one of the important commodities in Indonesia today and has quite promising development prospects, Pt. Toton Usaha Mandiri is an oil palm plantation, oil palm plantations are very profitabel so many forests are being converted into oil palm plantations, even though oil palm is very profitabel, it is very difficult to determine the amount of palm oil production in the future, therefore the author will predict the amount of palm oil production going forward with factors that influence palm oil production including demand, supply, production efficiency and variables related to palm oil production such as total income, total supply and total demand needed to achieve good production levels. One way to predict the rate of palm oil production is to use the C4.5 method. The C4.5 algorithm is an algorithm that can form a decision tree, where the decision tree will then produce new knowledge. In the target attribute, the amount of palm oil production is Satisfactory and Not Satisfactory. The analysis used is the C4.5 Algorithm which has a data sample of 54 data from 2019 to 2023 June. By processing the data using the Rapid Miner application, the system accuracy value was 96.30% the unsatisfactory prediction was 16 and the satisfactory prediction was 36 with a precision value of 94.12% and a recall value of 97.30%.